2010
DOI: 10.1152/ajpcell.00309.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone stimulates store-operated calcium entry and protein degradation in cultured L6 myotubes through a phospholipase A2-dependent mechanism

Abstract: Hasselgren PO. Dexamethasone stimulates store-operated calcium entry and protein degradation in cultured L6 myotubes through a phospholipase A 2-dependent mechanism. Am J Physiol Cell Physiol 298: C1127-C1139, 2010. First published January 27, 2010; doi:10.1152/ajpcell.00309.2009.-Muscle wasting in various catabolic conditions is at least in part regulated by glucocorticoids. Increased calcium levels have been reported in atrophying muscle. Mechanisms regulating calcium homeostasis in muscle wasting, in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 84 publications
2
16
0
Order By: Relevance
“…The critical role of VIA iPLA 2 for CCE was extensively investigated before (9,21,37). We have shown that the mechanism that underlies the increased load of the Ca 2ϩ stores and duration of the responses to ATP in LPStreated astrocytes is based on the increased CCE.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of VIA iPLA 2 for CCE was extensively investigated before (9,21,37). We have shown that the mechanism that underlies the increased load of the Ca 2ϩ stores and duration of the responses to ATP in LPStreated astrocytes is based on the increased CCE.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are significant because calcium is an important regulator of muscle protein breakdown [40]. In a recent study, we found evidence that glucocorticoids may increase muscle calcium levels secondary to stimulated store-operated calcium entry (SOCE) and that this effect of glucocorticoids was regulated by increased phospholipase A2 activity [41]. Additional experiments in the same study suggested that dexamethasone-induced protein degradation was calcium- and SOCE-dependent, suggesting that inhibition of SOCE may be a therapeutic tool to prevent glucocorticoid-induced muscle wasting.…”
Section: Other Novel Insight Into Mechanisms Regulating Glucocorticoimentioning
confidence: 99%
“…In previous studies, the increase in muscle proteolysis and changes in the expression of muscle wasting-associated transcription factors and nuclear cofactors during sepsis were more extensively prevented by RU38486 (1,36,45,53,57), supporting the concept that reduced muscle strength during early sepsis does not primarily reflect loss of muscle mass. Of note, we recently found that muscle calcium homeostasis, in particular store-operated calcium entry, is regulated by glucocorticoids (21), and it is possible that the effect of RU38486 observed in the present study reflected improved calcium homeostasis, although additional experiments are needed to test that hypothesis.…”
Section: Discussionmentioning
confidence: 65%